Balkan Smoke: Tobacco and the Making of Modern Bulgaria. - Mateusz Zatonski (Slovo, 2014)
By MARY C. NEUBURGER. Pp. 307. Ithaca: Cornell University Press. 2013. ISBN: 9780801450846. Click here to read article